BADONG SANG TORAYAAN PERUBAHAN BADONG PADA ORANG TORAJA - Ignea Restu Pampang; Erens Elvianus Koodoh (KABANTI : Jurnal Kerabat Antropologi, 2023)
This study aims to describe the original badong procession, describe the badong of the Toraja people in Kendary City, and analyze change in badong and the causes of changes in badong among Toraja people in Kendari city. of functionalism using the ethnographic method. The result of this indicicate that in the funeral procession the ma’badong ritual is carried out. This ritual usually carried aot as form of appreciation for people who have died by chanting badong poems containing an expression of lamentation, prayers and biographies of people who have returned to puang daring their life until they die. The procces of ma’badong carried out ini Kendary City is not much different from badong in Toraja because it does not change the value contained in the ritual. The only difference is the approval or agreement of the church and family so that the ritual is very rarely carried out. This happens because the family of the deceased has embraced Christianity and no longer embraces all todo lo (belief of the ancestors) so that ritual can be carried out if it has received approval from the family and the church. However, if one of them does not agree, then the ritual is not carried out. In addition, the change from badong did not experience significant changes in Kendary city because the duration of the in Maradona was not too long compared to badong in Toraja. Likewise, the uniform used by parading in Kendari city is not restricted/free compared to the pa’badong in Toraja who always wears a uniform equipped with a hat. this due to the economic factor of the deceased’s family which is not sufficient to finance all the needs of badong. Indeed, badong can be chanted at night after the consolation service after obtaining approval from family and church.